KONSEP KEKUDUSAN MENURUT IMAMAT 18 DAN IMPLIKASINYA TERHADAP KONSELING PRANIKAH KAUM MUDA - suhendra, Suhendra; Hutauruk, Ratna Juwita (UPPM Sekolah Tinggi Teologi Tabgha Batam, 2024)
Pre-marital counseling is an activity held for unmarried parties, in connection with their wedding plans. These parties come to the counselor to make their decisions so that they are more stable and can make better adjustments in the future. Marriage counseling or what is commonly called marriage counseling is an effort to help the prospective bride and groom. Marriage counseling is carried out by professional counselors. The goal is that they can develop and be able to solve the problems they face through ways of mutual respect, tolerance, and communication, in order to achieve family motivation, development, independence, and the welfare of all family members. In this journal, the researcher used a qualitative phenomenological approach, where in this research the emphasis is on meaning and process rather than the results of an activity Holiness is a state or quality of being holy. Holiness is a sign of a believer's spiritual life that must be continuously strived for, including ethical behavior. The Christian life and holiness are an inseparable unity in the believer. God's holiness has a lot to do with the people He chooses. Election/covenant is a unique expression of God's holiness. Because God is holy, God also requires His people to live holy lives (Leviticus 11:44). God shows His holiness in His actions for the salvation of the people He has chosen (Num. 20:13)